What is the effectiveness of combining warming mattresses and plastic bags versus plastic bags only for thermoregulation in preterm infants? A systematic review. Issue 1 (February 2020) - Langan, Miriam; Watson, C.; O'Connor, T.; Moore, Z.; Patton, D.
Abstract: Hypothermia is strongly associated with neonatal morbidities and mortality. There are several interventions to reduce the incidence of hypothermia following delivery. The aim of this systematic review was to compare the effectiveness of combining warming mattresses and plastic bags to plastic bags only for thermal regulation in preterm infants in the delivery suite and during stabilisation in the NICU. Four studies met the inclusion criteria. In comparison to the use of plastic bags only, the combination of warming mattresses and plastic bags reduces the incidence of hypothermia in preterm infants on admission to the NICU. However, there is a risk of hyperthermia. It is suggested that further research be carried out through more robust and rigorous methods.